Sensory and Chemical Evaluation of Jelly Candy with Honey Powder Substitution - Amertaningtyas, Dedes; Amalia, Alvina Wahyu; Evanuarini, Herly; Susilo, Agus; Jaya, Firman; Widati, Aris Sri; Azkarahman, Aldyon Restu; Masyithoh, Dewi (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
Jelly candy is a type of soft candy made from fruit extract, sugar, and gelatin. The high sugar content may have adverse health effects. Therefore, honey powder has potential as a partial sugar substitute as well as a functional ingredient. The aim of this study was to determine the best percentage of honey powder substitution to replace part of the sugar in milk jelly candy. The main raw material was cow’s milk with honey powder as a sugar (sucrose) substitute. The study used a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were T0 (25% sugar without honey powder), T1 (19% sugar + 6% honey powder), T2 (12.5% sugar + 12.5% honey powder), and T3 (6% sugar + 19% honey powder). The results showed that partial substitution of sugar with honey powder had a highly significant effect (p < 0.01) on reducing sugar (5.56-11.43%), antioxidant (90.16-116.73 ?g/mL), and color of sensory evaluation (3.58-4.05), as well as a significant effect (p < 0.05) on protein content (11.51-12.50%), taste (3.78-4.18), aroma (3.53-3.80), and overall acceptance (3.50-3.90), but no significant effect (p > 0.05) on texture (3.43-4.18). It can be concluded that substituting part of the sugar with honey powder in milk jelly candy affects the chemical properties. However, based on the evaluation, the control treatment with 25% sugar and no honey powder still be the most preferred product by panelists.